1992
DOI: 10.1029/90jb02473
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the tectonic regime above a subduction zone of Andean Type: The Andes of Peru and Bolivia during the Pliocene‐Pleistocene

Abstract: This paper adresses the changes in the tectonic regime in the Peruvian and Bolivian Andes that have occurred since the upper Miocene when the present‐day elevation of the Cordillera above sea level has been almost reached. The stress patterns are deduced essentially from a field study of fault kinematics and a numerical inversion of the slip vector data measured on the fault planes. The Cuzco fault system in southern Peru is chosen as an example to illustrate the methodology used. In this region, striations on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
85
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 71 publications
11
85
0
2
Order By: Relevance
“…The present day stress regime in southern Peru is controlled by: (1) north-south stretching, related to the extensional regime of the high Andean Cordillera and to the slow motion of the convergent plates, and; (2) east-west compression associated with the N80-trending convergent oceanic Nazca plate (Sébrier and Soler 1991;Mercier et al 1992). Moreover, data obtained with SPOT and SAR ERS-1 satellite images (Mering et al 1996) indicate that the tectonic regime in southern Peru close to Arequipa (Fig.…”
Section: Volcanism and Crustal Structure In The Andahuaorcopampa And mentioning
confidence: 94%
“…The present day stress regime in southern Peru is controlled by: (1) north-south stretching, related to the extensional regime of the high Andean Cordillera and to the slow motion of the convergent plates, and; (2) east-west compression associated with the N80-trending convergent oceanic Nazca plate (Sébrier and Soler 1991;Mercier et al 1992). Moreover, data obtained with SPOT and SAR ERS-1 satellite images (Mering et al 1996) indicate that the tectonic regime in southern Peru close to Arequipa (Fig.…”
Section: Volcanism and Crustal Structure In The Andahuaorcopampa And mentioning
confidence: 94%
“…Mercier et al (1992) suggested that weakening of the crust occurred for successive periods, probably extensional, during which the slab progressively lengthened and increased in depth, therefore favouring a seaward migration of the slab flexure. Thickening of the crust occurred during the compressional events (Sebrier and Soler, 1991), resulting from the rupture of a long, high-angle dipping slab under its own weight (Mercier et al, 1992). …”
mentioning
confidence: 99%
“…While the former two systems are associated with the Rio Tambo graben, the third system is minor and the last one consists of a series of sinistral, en echelon strike slip faults which are parallel to the Central Volcanic Zone (Lavallée et al unpublished). A study of fault kinematics by Mercier et al (1992) suggested that the mid-Pleistocene to present-day tectonic regime of the High Andes is characterized by a vertical maximum stress induced by the high elevation (>4,000 m), a secondary E-W compression caused by collision of the Pacific and South America plates, and a resulting N-S extension in the direction of σ3 (Fig. 1).…”
Section: Geological Settingmentioning
confidence: 98%
“…This ancestral volcano consists of 500 m of andesite porphyry of the Pastillo volcanic complex (James Lavallée, 2003). The current stress vectors of the High Andes are indicated in the inset (Mercier et al 1992). The location of earthquakes that occurred in the area since 1471 are indicated by a circle, which includes the depth estimate (Ceresis, 1985 Tosdal et al 1981;INGEMMET 2000a).…”
Section: Geological Settingmentioning
confidence: 99%